Incidence, Prevalence, and Mortality of People with Psoriasis and Psoriatic Arthritis in Taiwan: A Nationwide Cohort Study - Ireny Y.K. Iskandar; Teng-Chou Chen; Li-Chia Chen; Meng-Sui Lee; Yen-Yun Yang; Ting-Chun Wang; Yu-Chun Hsieh; K. Arnold Chan; Christopher E.M. Griffiths; Darren M. Ashcroft (Medical Journals Sweden, 2022)
There is a recognized need to better understand changes in the epidemiology of psoriasis and psoriatic arthritis (PsA) over time in Asia. Using the Taiwan National Health Insurance claim records this population-based study examined changes in the prevalence, incidence, and mortality rates in patients with psoriasis or psoriatic arthritis in Taiwan over 12 years. Patients with ≥1 diagnosis code for psoriasis or psoriatic arthritis, recorded either by dermatologists or rheumatologists, were identified. Annual age- and sex-standardized prevalence and incidence rates were calculated using the Taiwan general population as reference. To investigate mortality, each patient in the incident cohort was matched to 10 comparators from the general population by sex and age (at diagnosis). The risk of mortality between study cohorts and comparators was analysed by Cox proportional hazard regression. The prevalence of psoriasis (0.18-0.86%) and psoriatic arthritis (0.01-0.08%) increased steadily between 2006 and 2017. The incidence rates, however, remained stable (psoriasis: 62-65 per 100,000 person-years; psoriatic arthritis: 6-5 per 100,000 person-years). The risk of all-cause mortality for patients with psoriasis (hazard ratio 1.16; 95% confidence interval: 1.13-1.19) was higher than the general population, despite a decreasing trend over time in the all-cause mortality rates for both groups. The steady increase in the prevalence of psoriasis despite stable incidence rates suggests that improvements in life expectancy may be the key determinant of this increase.